PENGARUH PROFITABILITAS DAN FINANCIAL LEVERAGE TERHADAP KEBIJAKAN DIVIDEN SERTA DAMPAKNYA TERHADAP HARGA SAHAM (Studi pada Emiten Manufaktur Industri Barang Konsumsi di Bursa Efek Indonesia periode 2007-2012) - Rahmah Yulianti; Muhammad Arfan; Said Musnadi (Jurnal Telaah dan Riset Akuntansi, 2014)
ABSTRACT The objective of this research is to study influence of profitability, financial leverage on dividend policy and its effect on stock price. Profitability is measured by ROA (X1), financial leverage is measured by DER (X2), dividend policy is measured by dividend payout ratio (Y) on stock price (Z) is measured with price per share when closed price. The population of this study is consume goods companies. This research uses 48 companies from  2007 to 2012 (pooled data). Sample selection applies sensus techniques and criteria thus obtained 8 companies. Analysis of data used is path analysis with SPSS program.            Keyword: Divident policy (Divident Payout Ratio), Stock price (closing price), Profitability (Return on Assets), and Financial leverage (Debt to Equity Ratio).